Tolerance to Central Hypovolemia Is Greater Following Caffeinated Coffee Consumption in Habituated Users - Pizzey, Faith K.; Tourula, Erica; Pearson, James (Frontiers in Physiology, 2020)
We investigated the influence of caffeinated coffee consumption on cardiovascular responses and tolerance to central hypovolemia in individuals habituated to caffeine. Thirteen participants completed three trials, consuming caffeinated coffee, decaffeinated coffee or water before exposure to central hypovolemia via lower body negative pressure (LBNP) to pre syncope. Tolerance to central hypovolemia was quantified as cumulative stress index (CSI: LBNP level multiplied by time; mmHg*min). Prior to the consumption of caffeinated coffee, decaffeinated coffee and water, heart rate (HR: 62±10, 63±9 and 61±8 BPM, respectively), stroke volume (SV: 103±23, 103±17 and 102±18 mL/beat, respectively) and total peripheral resistance (TPR: 14.2±3.0, 14.0±3.0 and 14.3±2.7 mmHg/L/min, respectively) were not different between trials (all P > 0.05). Mean arterial pressure (MAP) increased following consumption of all drinks (Post Drink) (Caffeinated coffee: from 86±8 to 97±7; Decaffeinated coffee: from 88±10 to 94±7; and Water: from 87±10 to 96±6 mmHg; all P = 0.0001) but was not different between trials (P = 0.247). During LBNP, HR increased (P = 0.000) while stroke volume decreased (P = 0.000) relative to post drink values and TPR as unchanged (P = 0.109). HR, SV and TPR were not different between trials (all P > 0.05). MAP decreased at pre syncope in all trials (60±5, 60±7 and 61±6 mmHg; P<0.001). LBNP tolerance was greater following caffeinated coffee (914±309 mmHg*min) relative to decaffeinated coffee and water (723±336 and 769±337 mmHg*min, respectively, both P < 0.05). Tolerance to central hypovolemia was greater following consumption of caffeinated coffee in habituated users.